Antibiotic‐tolerantStaphylococcus aureusBiofilm Persists on Arthroplasty Materials. Issue 7 (July 2016) - Urish, Kenneth L.; DeMuth, Peter W.; Kwan, Brian W.; Craft, David W.; Ma, Dongzhu; Haider, Hani; Tuan, Rocky S.; Wood, Thomas K.; Davis, Charles M.
Abstract: Background: The continued presence of biofilm may be one cause of the high risk of failure observed with irrigation and débridement with component retention in acute periprosthetic joint infection (PJI). There is a poor understanding of the role of biofilm antibiotic tolerance in PJI. Questions/purposes: (1) Do increasing doses of cefazolin result in decreased viable biofilm mass on arthroplasty materials? (2) Is cefazolin resistance phenotypic or genotypic? (3) Is biofilm viability a function of biofilm depth after treatment with cefazolin? (4) Is the toxin‐antitoxin system, yoeB expression, associated with antibiotic stress? Methods: Methicillin‐sensitive Staphylococcus aureus biofilm was cultured on total knee arthroplasty (TKA) materials and exposed to increasing doses of cefazolin (control, 0.5, 1.0, 10.0, 100.0 μg/mL). Quantitative confocal microscopy and quantitative culture were used to measure viable biofilm cell density. To determine if cefazolin resistance was phenotypic or genotypic, we measured minimum inhibitory concentration (MIC) after exposure to different cefazolin concentrations; changes in MIC would suggest genotypic features, whereas unchanged MIC would suggest phenotypic behavior. Finally, quantitative reverse transcription‐polymerase chain reaction was used to quantify expression of yoeB levels between biofilm and planktonic bacteria after exposure to 1 μg/mL cefazolin for 3 hours. Results: Although live biofilm mass was reduced by exposure to cefazolin when compared with biofilm mass in controls (39.2 × 10 3 ± 26.4 × 10 3 pixels), where the level after 0.5 μg/mL exposure also showed reduced mass (20.3 × 10 3 ± 11.9 × 10 3 pixels), no further reduction was seen after higher doses (mass at 1.0 μg/mL: 5.0 × 10 3 pixels ± 1.1 × 10 3 pixels; at 10.0 μg/mL: 6.4 × 10 3 ± 9.6 × 10 3 pixels; at 100.0 μg/mL: 6.4 × 10 3 ± 3.9 × 10 3 ). At the highest concentration tested (100 μg/mL), residual viable biofilm was present on all three materials, and there were no differences in percent biofilm survival among cobalt‐chromium (18.5% ± 15.1%), polymethylmethacrylate (22.8% ± 20.2%), and polyethylene (14.7% ± 10.4%). We found that tolerance was a phenotypic phenomenon, because increasing cefazolin exposure did not result in changes in MIC as compared with controls (MIC in controls: 0.13 ± 0.02; at 0.5 μg/mL: 0.13 ± 0.001, p = 0.96; at 1.0 μg/m: 0.14 ± 0.04, p = 0.95; at 10.0 μg/m: 0.11 ± 0.016, p = 0.47; at 100.0 μg/m: 0.94 ± 0.047, p = 0.47). Expression of yoeB after 1 μg/mL cefazolin for 3 hours in biofilm cells was greater in biofilm but not in planktonic cells (biofilm: 62.3‐fold change, planktonic cells: −78.8‐fold change, p < 0.001). Conclusions: Antibiotics are inadequate at complete removal of the biofilm from the surface of TKA materials. Results suggest that bacterial persisters are responsible for this phenotypic behavior allowing biofilm high tolerance to antibiotics. Clinical Relevance: Antibiotic‐tolerant biofilm suggests a mechanism behind the poor results in irrigation and débridement for acute TKA PJI.